ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL CERITA BERDASARKAN ANALISIS NEWMAN DI KELAS X SMA INTENSIF TARUNA PEMBANGUNAN SURABAYA - Moh.Syukron Maftuh (Buana Matematika : Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2019)
This research is a descriptive study with a quantitative approach. The subjects of this study were 34 students of class X MIA 2 SMA Taruna Pembangunan Intensive School academic year 2019/2020 who were then given a written test in the form of a story, and 3 students who made the most mistakes were taken to be interviewed. Then the data obtained were carried out to have data reduction, data presentation in tabular form to be described, and then conclusions were drawn. Based on the results of data analysis, it was obtained that (1) At the reading stage, students did not experience difficulties, so there was no error at the reading stage; (2) In the stage of understanding, mistakes made by students were 37.15% which included errors when identifying commands on the problem, so it was wrong in determining what was known and what was asked in the problem and making mistakes in changing the context of the problem of the story into its own language that affected the process of problem solving; (3) At the transformation stage, the errors conducted by students were 13.04% including students were unable to translate their mistakes and transform the existing formations in the problem into the form of mathematical sentences, as well as a lack of understanding to use the method to be used; (4) In the process skills stage, the mistakes made by students were 20.94% including students still made mistakes in the calculation process such as when transferring terms into different segments and adding two terms with the same variable. In addition, students also made mistakes in the process of elimination and substitution when performing multiplication, addition, and subtraction operations as well as lack of understanding of what operations would be used; and (5) At the stage of writing the final answer, the mistakes made by students were 28.85% including students did not write the conclusions of the solutions obtained correctly, even some students did not change the solutions obtained in the form of sentences in accordance with the real problems known in the tests.